Clinical Hypertension - Chung, Wook-Jin.; Pyun, Wook Bum.; Cho, In-Jeong.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Clinical Hypertension is the official journal of the Korean Society of Hypertension, and the Korean Society of Pulmonary Hypertension. Clinical Hypertension is a peer-reviewed, open access journal that aims to publish in all areas of hypertension and vascular disorders. We aim to ensure the widest possible dissemination of research throughout the hypertension community. The journal focuses on areas within vascular biology, cellular and molecular biology, clinical hypertension, epidemiology, nephrology, endocrinology, neuroscience, pharmacology, genetics, pediatric hypertension and basic science. Clinical Hypertension is a continuation of the Korean journal, Journal of the Korean Society of Hypertension.
Keywords: Cardiology; Blood-vessels$1 (BDiseases.s; Internal medicine; Public health; Cardiology; Angiology; Internal Medicine; Public Health